KARAKTERISASI ALTERASI HIDROTHERMAL DAN MINERALISASI BIJIH PROSPEK DARKNIR SEBAGAI INDIKASI SISTEM ENDAPAN MINERAL PORPHYRY CU-AU, DISKTRIK OKSIBIL, KABUPATEN PENGUNUNGAN BINTANG, PROVINSI PAPUA PENGUNUNGAN - David Suhendi, Dirga
This research was conducted at the Darknir Prospect, located in the Segnam Block, Oksibil District, Pegunungan Bintang Regency, Papua Pegunungan Province, Indonesia. The background of this study stems from exploration activities carried out in 2019-2020 by the Geomin Unit of PT Antam Tbk at the Darknir Prospect, which did not involve comprehensive analysis, particularly in justifying the drilling of DSG-19-001. Therefore, this research aims to conduct a more in-depth analysis by utilizing lithological, alteration, geochemical, and geophysical data to provide a more complete understanding of the mineralization system developing at the Darknir Prospect. The methodology used in this study involves the analysis of geological mapping data, soil sampling data, groundmagnetic geophysical survey data, and core drilling data from DSG- 19-001. The Darknir Prospect consists of intrusive plutonic rocks, including hornblendebiotite diorite (HBD) and monzodiorite (MZD), originating from the Antares complex, which is intruded by porphyritic basaltic andesite (BAP), biotite diorite (BTD), and quartz monzodiorite (QMD). The alteration at this prospect is dominated by chloritic alteration, which is divided into outer and inner propylitic zones; in addition, sericitic and argillic alterations are also present in structural zones. Drilling DSG-19-001 at the Darknir Prospect was conducted at a location with Cu and Mo anomalies based on geological mapping and soil sampling results. This drilling also considered groundmagnetic geophysical data, which showed high magnetic values, presumed to be an intrusion carrying porphyry mineralization. The drilling intercepts of DSG-19-001 are divided into six zones: garnet alteration zone, low and intermediate sulfidation quartz vein zone, outer porphyry "D" vein zone, inner porphyry "D" vein zone, outer porphyry "B" vein zone, and inner porphyry "B" vein zone, with these zones being classified based on mineralization characteristics. The DSG-19-001 drilling is also interpreted to have penetrated the outer portion of the porphyry mineral deposit system, characterized by intersecting "B" veins within propylitic-altered rocks, with the best intercept being 133.85 m @ 0.1% Cu, 28.4 ppm Mo, and 0.03 ppm Au at a depth of 700 – 833.85 m. The central zone of porphyry mineralization, which potentially contains higher copper-molybdenum grades, has not yet been reached by DSG-19-001 drilling at the Darknir Prospect. Nevertheless, there is an increase in Cu and Mo grades with increasing borehole depth, accompanied by rising magnetic susceptibility values and the presence of chalcopyrite and molybdenite mineralization. These findings reinforce the belief that Cu-Mo mineralization in DSG-19-001 drilling remains open to depth, making this prospect very attractive for further exploration.